Contribution of Performance Management System to Myanmar Corporate Performance - Aung, Htet Htet; Lee, Kar Ling (INTI International University, 2018)
Performance management encompasses both individual and corporate performance. The introduction and implementation of a performance management system carries profound implications for both employees and organisations and thus, many organisations tended to spend much on such system. Generally, organisations invest huge amounts of financial and non-financial resources on performance management systems, and it is important that such systems are owned and used effectively by all concerned. However, the effectiveness of such performance management system is mixed and thus, there is a need to conduct such a study especially within the context of Myanmar as the country is growing in a dynamic manner and the performance of the corporations are of importance to ensure continued growth to sustain the growth of Myanmar as a country and the corporations specifically.